Evaluation of the national cervical cancer screening program in Morocco: achievements and challenges. (September 2019) - Selmouni, Farida; Belakhel, Latifa; Sauvaget, Catherine; Abousselham, Loubna; Lucas, Eric; Muwonge, Richard; Sankaranarayanan, Rengaswamy; Khazraji, Youssef Chami; Basu, Partha
Objectives: To report the key outcomes of evaluation of the national cervical cancer screening program in Morocco, and describe its organization, status of implementation, performance, and major challenges. Methods: An evaluation team conducted program manager interviews and screening provider focus group discussions, supervisory visits to primary health and diagnostic centers, and review of published documents. Aggregated performance data collected by the Ministry of Health from the screening and diagnostic centers were analyzed. Results: Screening is conducted using visual inspection with acetic acid. The program is opportunistic, with no mechanism to identify and invite eligible women. Coverage of the target population was very low (6.6% in 2015 and 7.7% in 2016). Positivity rates were 5.3% and 8.9% in 2015 and 2016 respectively, and varied widely between regions. Detection rate of cervical intraepithelial neoplasia (CIN) 2 or worse in 2016 was very low (0.9/1, 000), with more invasive cancers detected than CIN 2/3. Lack of histopathology and treatment facilities at the Cancer Early Detection Centers is a major short-coming, and there is a need for service-provider refresher training. Without a computerized health information system tracking screen positive women, ensuring high treatment compliance and performing regular quality assurance are challenging. Conclusions: The screening program in Morocco requires better organization, a pragmatic system of inviting the target population, improved compliance to diagnosis, treatment, and follow-up, improved provider training, better quality assurance systems, and an effective health information system with appropriate linkages for monitoring and evaluation.